Szkolne nauczanie religii wobec zadania przygotowania młodzieży do konstruktywnego rozwiązywania konfliktów w małżeństwie i rodzinie - Zellma, Anna (Studia Pastoralne, 2009)
Religious education faces various educational tasks at school. The tasks focus on teaching and integral upbringing. They involve further and closer preparation of the youth to married and family life. Conflicts in married and family life and developing appropriate skills seem an essential thematic category for religious education. This article is aimed at finding answers to the following questions: how are the problems related to conflicts in married and family life dealt with in religious education classes at school and how is the task of the preparation of the youth to constructive conflict solving in married and family life carried out. While answering these questions, the religious curriculum at upper secondary school, lower secondary school, and at professional schools are referred to. In order to better understand the issue and to show it in the context of social science, first conflicts in married and family life are presented from a psychological and pedagogical perspective. Next, religious education matters are shown. The analyses carried out here are of theoretical nature only. They are based on religious curriculums at various types of comprehensive, secondary and professional schools.